The roles of TNFAIP2 in cancers and infectious diseases. Issue 11 (25th August 2018) - Jia, Lin; Shi, Yundong; Wen, Yi; Li, Wei; Feng, Jing; Chen, Ceshi
Abstract: TNFα‐induced protein 2 (TNFAIP2) is a primary response gene of TNFα. TNFAIP2 is highly expressed in immune cells and the urinary bladder. The expression of TNFAIP2 is regulated by multiple transcription factors and signalling pathways, including NF‐κB, KLF5 and retinoic acid. Physiologically, TNFAIP2 appears to be a multiple functional mediator not only for inflammation, angiogenesis and tunneling nanotube (TNT) formation but also as a regulator of cell proliferation and migration. The expression of TNFAIP2 is frequently abnormal in human cancers and in infectious diseases. Due to its significant functions in cell proliferation, angiogenesis, migration and invasion, TNFAIP2 could be a potential diagnostic biomarker and therapeutic target for cancer.